Effect of DASH diet on oxidative stress parameters: A systematic review and meta-analysis of randomized clinical trials. Issue 6 (November 2020) - Pirouzeh, Razieh; Heidarzadeh-Esfahani, Neda; Morvaridzadeh, Mojgan; Izadi, Azimeh; Yosaee, Somaye; Potter, Eric; Heshmati, Javad; Pizarro, Ana Beatriz; Omidi, Amirhosein; Heshmati, Shilan
Abstract: Background and aims: Oxidative stress (OS) is one of the main risk factors for several chronic diseases. The Dietary Approaches to Stop Hypertension (DASH) contain many antioxidants and may contribute to managing OS. Objective: To perform a systematic review and meta-analysis to examine the impacts of the DASH diet on OS parameters. Methods: A comprehensive electronic search in MEDLINE, Scopus, EMBASE, and the Cochrane Central Register of Controlled Trials was performed through September 2020 to find related studies evaluating the impact of the DASH diet on OS parameters. Standardized mean differences were pooled using random-effects meta-analysis. Results: Eight studies with a total of 317 subjects met our inclusion criteria. Four studies included in meta-analysis model with 200 participants (100 in treatment and 100 in control group). The DASH diet was associated with a statistically significant decrease in malondialdehyde (MDA) (SMD: −0.53; 95% CI: −0.89,  −0.16; I 2  = 42.1%), and a significant increase in glutathione (GSH) (SMD: 0.83; 95% CI: 0.36, 1.03; I 2  = 42.1%). Meta-analysis found no statistically significant effect of DASH diet on nitric oxide (NO) (SMD: −1.40; 95% CI: −0.12, 1.93; I 2  = 92.6%) or total antioxidant capacity (TAC) levels (SMD: 0.95; 95% CI: −0.10, 1.99; I 2  = 87.6%). Conclusion: Our results demonstrated that a DASH diet could significantly increase GSH and decrease MDA levels. Furthermore, there is a trend to improve TAC, NO, and f2-isoprostanes by the adherence to the DASH diet. However, long-term, large sample size and well-designed randomized clinical trials are still needed to draw concrete conclusions about DASH diet's effects on OS parameters. Highlights: DASH diet could significantly increase glutathione levels. DASH diet could decrease lipid peroxidation and malondialdehyde (MDA) levels. The DASH diet can improve the antioxidant defense of the body and decrease oxidative stress.